Subsidios habitacionales, reactivación económica y distribución del ingreso: Santiago de Chile, 1983 - Necochea, Andrés (Revista EURE - Revista de Estudios Urbano Regionales, 1986)
Andrés Necochea analizes the subsidies involved in the chilean housing policy in the Metropolitan Area of Santiago. The policy was stated in 1977, as a modification of the previous ones, under the assumption that they had benefited primarily the higher income groups; its objective was highly redistributive and was aimed at the poorer groups lacking adequate housing conditions. The article demonstrates that the new strategy, based on the market and operating in a highly recessive context for the economy as a whole (1983) was even more regressive than the previous ones, and that it had very small effects over the reactivation of the sector.